In vitro analysis of collagen-chitosan scaffold loaded with metronidazole nanoparticle for periodontal disease treatment - Mohd Zayi, Nora Azirah; Halim, Lutfi; Harun @ Ismail, Ahmad Fahmi; Mohamad, Mohd Yusof (Taylor & Francis, 2025)
Periodontal diseases pose significant challenges to oral health, often requiring advanced therapeutic interventions involving the utilization of three-dimensional (3D) scaffolds, However, this intervention could not prevent inflammatory reactions. Hence, recent years have seen a growing emphasis on developing new antibacterial scaffolds in dental tissue engineering. This study aimed to address these challenges by evaluating the antibacterial and biocompatibility properties of a novel collagen-chitosan scaffold loaded with metronidazole nanoparticles (CC-MT) for periodontal therapy. The antibacterial activity of CC-MT against Porphyromonas gingivalis and Fusobacterium nucleatum was assessed using the disk diffusion test. Additionally, cytocompatibility was evaluated by examining cell viability and proliferation using Human Gingival Fibroblast cells (HGF-1), and cell attachment was characterized using filed emission scanning electron microscopy. Our findings revealed that CC-MT exhibited antibacterial effects against the pathogens, with CC-MT (30% metronidazole) showing a higher inhibitory effect, with no significant difference compared to the positive control (metronidazole disc) (p < 0.05). In addition, in vitro cell culture studies revealed that the CC-MT (30% metronidazole) has no negative effect on cell morphology, viability, and proliferation and possesses good biocompatibility. Based on these results, CC-MT demonstrated potential as drug carriers and could be promising candidates for the treatment of periodontal disease.